The effects of the coordination on the fragmentation of a single grain. (August 2015) - Salami, Y; Dano, C; Hicher, P-Y; Colombo, G; Denain, P
Abstract: The main objective of this study is to understand the effects of the coordination number on the behavior of a single grain, before and during fracture. A new apparatus is designed, with the purpose of conducting multipoint crushing tests, and to investigate the effects of the contacts number, type and position on the failure of a particle. Some of the tests were monitored using digital image correlation (DIC), in order to get an in-depth view into the mechanics of fracture. The fragmentation of the grains was studied, and the cracks were shown to follow specific paths. The failure forces of multiple contact configurations were compared to show the effect of the number and position of contact forces on the primary and secondary cracks. It was shown that the position and magnitude of the contact forces plays a significant role in the fragmentation of the grain.